Baczko and the French Revolution. Plot of an Imaginary - Alessandro Guerra (Scienza & Politica)
The essay reconstructs Baczko’s thinking on the French Revolution. Founded on Enlightenment progress, the Revolution had inaugurated a political space open to utopia. The men who brought about political change and were shaped by revolutionary events did not delegate the realisation of their projects of social innovation to political power. Thermidor serves Baczko to develop an original reading of terror, i.e. the fears that the revolutionaries had nurtured in order to dismantle all opposition and neutralise any vague attempts at resistance. Terror thus becomes the violence that radicalises the egalitarian idea brought by the Enlightenment and at the same time betrays its ideals.